Investigating the Factors Affecting the Growth of Tourism in Kabale Municipality. - Amiidu, Muriisa (Kabale University, 2024)
The study was about the examining the factors that affect the growth of tourism in Kabale municipality, Kabale district. The study was guided by three objectives which were: to identify the key factors influencing the growth of tourism in Kabale municipality, to examine how government policy has contributed to the tourism in Kabale district, and to suggest possible measures for the constraints affecting tourism growth in Kabale District. A targeted population of 56 respondents was considered for the study which included district Leaders and staff members. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on results from the study, 100% of the respondents agreed that potential factors that have led to the growth in the Kabale district include; environment and events, community perception, accessibility of infrastructure, good reception, lodge owners and managers, natural attraction, perceived safety and security and Perceived safety and security. The study findings revealed how government policy has contributed to tourism in Kabale district were presented in the table and these included consolidating and streamlining the law relating to tourism. Providing licensing, regulating, and controlling of the tourism sector, strategic considerations for the development of new products. From objective three, it was found as indicated by the respondents from the Kabale district that that, there the potential factors that have led to the growth in the Kabale district. The results further indicated among the possible constraints to tourism development in Kabale Municipality, Kabale District and how can the constraints to tourism in Kabale District be mitigated/reduced include; poor hotels, distance and high transport costs, low pay for tour guides, language barrier, high priorities for international tourism by government, insecurity, poor road. The researcher concluded that the attractions that Influence the Growth of Tourism are game and bird viewing, quality accommodation, tour operators, image of destination, boating and water sports, craft shops, and tourism centers. The study findings recommend that there is a need to educate the citizens on how to be hospital to tourists and educate them on the importance of tourism in the area